MODERN VIEW ON DIAGNOSTICS AND TREATMENT OF GLUTEN ENTEROPATHY IN INFANTS - T. M. Osheva; N. S. Zhuravlyeva; O. V. Osipenko (Вопросы современной педиатрии)
Gluten enteropathy is a hereditary disease of the small intestine. It is characterized by the intolerance of specific cereal proteins leading to development of hyperregenerative atrophy of the small intestine mucous membrane. The diagnosis is based on complex evaluation of clinical, serological, endoscopic and morphological findings. The correctness of the diagnosis is confirmed by the reverse development of the morphological changes at the background of gliadin free diet.